Modeling functional material - Wang, Yating. (2012)
This report is a conclusion of what have been learned from the final year project which title is modeling functional materials by the author as a student during the period of final year project research. The aim of this one year project is to do research and learn more knowledge based on what the author have learned after four year university life time. In this period, she read books, journals and papers to get the knowledge about the function of one type of functional materials (which is one aromatic oligoamide--circular aromatic pentamers) and how to synthesis this functional material which is one and the function of this functional material. After that, the author suggests some other possible methods to synthesis this functional material. These are all consolidated in this report. The project helps the author to get a general idea of what are functions of this functional material and how can this functional material can be synthesized. More details like the functions of this functional material, process of synthesizing circular aromatic pentamers and suggestions for process of synthesizing circular aromatic pentamers are given in this report.